PNA- and SBA-positive lymphocytes content in the major salivary glands' structures during early postnatal period after intrauterine antigenic action - І. N. Maslova (Zaporozhye State Medical University, 2014)
Aim - to determine the Peanut agglutinin- and Soybean agglutinin-positive (PNA+, SBA+) lymphocytes content in the major salivary glands' structures in early postnatal period after intrauterine antigenic action. Methods and results. 224 submandibular salivary glands of white laboratory rats were investigated through the lectinhistochemical and statistical methods. Conclusions. In newborn animals after intrauterine antigen action the increased content of PNA+ intraepithelial lymphocytes and PNA+ stromal lymphocytes of major salivary glands was determined as compared to control group. That tendency remains till the 14th day, gradually decreasing till the 45th day of postnatal formation. Quantity of SBA+ lymphocytes decreased in antigenpremium animals as compared with control group animals. In addition, the quantity of SBA+ lymphocytes in experimental group remains lower during two weeks after birth. On the 45th day ofpostnatal formation the findings do not differ among experimental animals.